Patients as Customers. A Comparative Study on Patient's Satisfaction in Private and Public Medical Practice - Lebedeva, Yuliya; Štěrbová, Ludmila, 1957-; Fidler, Armin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The research paper is analysing patients as customers and compares patient satisfaction in public and private medical practices. Previous Austrian hospital efficiency studies date back to the 1990s, thus this thesis aims to address the situation as it is nowadays. The area of patient satisfaction is of particular interest to the healthcare sector in the view of its association with increased financial gains, improved patients’ compliance with treatment, the prospect of coming back again, reduced employee turnover and decreased malpractice claims. The primary study objectives encompass assessing the level of patient satisfaction towards the healthcare services provided in the public and private hospitals, correlate the levels of patient satisfaction with the focal points of the HEALTHQUAL model laid down in the questionnaire, and to compare and critically analyse patient satisfaction between the two institutions. Moreover, the study correlates its primary findings with patients’ socio-demographic variables, namely age, gender, education level. Primary research was conducted by disseminating structured questionnaires in the public and the private hospital, constituting of the 14 statements to be evaluated on a 5-point Likert scale and 3 questions on the socio-demographic background. The results were presented by using frequency, percentage, minimum and maximum, mean, standard deviation as well as the Spearman’s rs coefficient being applied to detect correlations between the findings present, if any. The findings of the primary data were analysed alongside the literature review. Given research revealed no apparent differences in patient perceptions of the total quality service and confirmed the major determinant being patient expectations.
Moreover, no strong correlation has been identified between the patient satisfaction levels and the socio-demographic variables, except for gender – female patients appeared to be less satisfied with the medical services provided than male patients. The analysis of the research findings and conclusion allowed the author to recommend both healthcare institutions to improve certain aspects of the healthcare services provided, suggest the private hospital to re-evaluate its strategy keeping patient expectations in mind, as well as provide some recommendations for future research.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses